Chemokine receptor CXCR4 activates the RhoA/ROCK2 pathway in spinal neurons that induces bone cancer pain. (April 2020) - Xu, Heng; Peng, Chong; Chen, Xue-Tai; Yao, Ying-Ying; Chen, Li-Ping; Yin, Qin; Shen, Wen
Background: Chemokine receptor CXCR4 has been found to be associated with spinal neuron and glial cell activation during bone cancer pain. However, the underlying mechanism remains unknown. Furthermore, the RhoA/ROCK2 pathway serves as a downstream pathway activated by CXCR4 during bone cancer pain. We first validated the increase in the expressions of CXCR4, p-RhoA, and p-ROCK2 in the spinal dorsal horn of a well-characterized tumor cell implantation-induced cancer pain rat model and how these expressions contributed to the pain behavior in tumor cell implantation rats. We hypothesized that spinal blockade of the CXCR4-RhoA/ROCK2 pathway is a potential analgesic therapy for cancer pain management. Methods: Adult female Sprague–Dawley rats (body weight of 180–220 g) and six- to seven-week old female Sprague–Dawley rats (body weight of 80–90 g) were taken. Ascitic cancer cells were extracted from the rats (body weight of 80–90 g) with intraperitoneally implanted Walker 256 mammary gland carcinoma cells. Walker 256 rat mammary gland carcinoma cells were then injected (tumor cell implantation) into the intramedullary space of the tibia to establish a rat model of bone cancer pain. Results: We found increased expressions of CXCR4, p-RhoA, and p-ROCK2 in the neurons in the spinal cord. p-RhoA and p-ROCK2 were co-expressed in the neurons and promoted by overexpressed CXCR4. Intrathecal delivery of CXCR4 inhibitor Plerixafor (AMD3100) or ROCK2 inhibitor Fasudil abrogated tumor cell implantation-induced pain hypersensitivity and tumor cell implantation-induced increase in p-RhoA and p-ROCK2 expressions. Intrathecal injection of stromal-derived factor-1, the principal ligand for CXCR4, accelerated p-RhoA expression in naive rats, which was prevented by postadministration of CXCR4 inhibitor Plerixafor (AMD3100) or ROCK2 inhibitor Fasudil. Conclusions: Collectively, the spinal RhoA/ROCK2 pathway could be a critical downstream target for CXCR4-mediated neuronal sensitization and pain hypersensitivity in bone cancer pain, and it may serve as a potent therapeutic target for pain treatment.